Frequency and format of clinical trial results dissemination to patients: a survey of authors of trials indexed in PubMed. Issue 10 (21st October 2019) - Schroter, Sara; Price, Amy; Malički, Mario; Richards, Tessa; Clarke, Mike
Abstract : Objective: Dissemination of research findings is central to research integrity and promoting discussion of new knowledge and its potential for translation into practice and policy. We investigated the frequency and format of dissemination to trial participants and patient groups. Design: Survey of authors of clinical trials indexed in PubMed in 2014–2015. Results: Questionnaire emailed to 19 321 authors; 3127 responses received (16%). Of these 3127 trials, 2690 had human participants and 1818 enrolled individual patients. Among the 1818, 498 authors (27%) reported having disseminated results to participants, 238 (13%) planned to do so, 600 (33%) did not plan to, 176 (10%) were unsure and 306 (17%) indicated 'other' or did not answer. Of the 498 authors who had disseminated, 198 (40%) shared academic reports, 252 (51%) shared lay reports, 111 (22%) shared both and 164 (33%) provided individualised study results. Of the 1818 trials, 577 authors (32%) shared/planned to share results with patients outside their trial by direct contact with charities/patient groups, 401 (22%) via patient communities, 845 (46%) via presentations at conferences with patient representation, 494 (27%) via mainstream media and 708 (39%) by online lay summaries. Relatively few of the 1818 authors reported dissemination was suggested by institutional bodies: 314 (17%) of funders reportedly suggested dissemination to trial participants, 252 (14%) to patient groups; 333 (18%) of ethical review boards reportedly suggested dissemination to trial participants, 148 (8%) to patient groups. Authors described many barriers to dissemination. Conclusion: Fewer than half the respondents had disseminated to participants (or planned to) and only half of those who had disseminated shared lay reports. Motivation to disseminate results to participants appears to arise within research teams rather than being incentivised by institutional bodies. Multiple factors need to be considered and various steps taken to facilitate wide dissemination of research to participants.